From Chalkboard Era to Digital Literacy Era: The Impact of Audio-Visual Tools on Modern Classroom at Secondary School Teachers in District Kot Addu South Pakistan - Muhammad Kashif Majeed Chaudhary; Tunku Badariah Binti Tunku Ahmad (UIN Raden Mas Said Surakarta, 2026)
The rapid advancement of digital technology has transformed educational practices, particularly in secondary education, by encouraging the integration of audio-visual tools into classroom instruction. This study examined secondary school teachers' perceptions of audio-visual tools and compared multimedia projector-based instruction with traditional chalkboard teaching in District Kot Addu, South Pakistan. A quantitative research design was employed using a structured questionnaire administered to 500 secondary school teachers. Data were analyzed using descriptive statistics, independent-samples t-tests, and Cohen's d effect size analysis. The findings revealed that teachers generally perceived audio-visual tools as valuable resources for enhancing classroom instruction, although perceptions varied across districts. Multimedia projector-based instruction received significantly higher ratings than traditional chalkboard teaching (t(138) = –2.88, p = .005, d = 0.73), indicating a meaningful preference for technology-supported learning. Significant gender differences were also identified, with female teachers reporting more positive perceptions of audio-visual tools than male teachers (t(118) = –2.45, p = .016, d = 0.80), suggesting that these differences were both statistically and educationally meaningful. Overall, the findings highlight the growing importance of digital instructional media in facilitating the transition from conventional teaching to technology-enhanced learning environments. The study recommends strengthening multimedia infrastructure, expanding teachers' digital competence through continuous professional development, and ensuring equitable access to educational technologies across schools.